Species Diversity and Ecological Habitat of Absidia (Cunninghamellaceae, Mucorales) with Emphasis on Five New Species from Forest and Grassland Soil in China - Heng Zhao; Yong Nie; Tong-Kai Zong; Yu-Jie Wang; Mu Wang; Yu-Cheng Dai; Xiao-Yong Liu (Journal of Fungi, 2022)
Although species of Absidia are known to be ubiquitous in soil, animal dung, and insect and plant debris, the species diversity of the genus and their ecological habitats have not been sufficiently investigated. In this study, we describe five new species of Absidia from forest and grassland soils in southwestern China, with support provided by phylogenetic, morphological, and physiological evidence. The species diversity and ecological habitat of Absidia are summarized. Currently, 22 species are recorded in China, which mainly occur in soil, especially in tropical and subtropical forests and mountains. An updated key to the species of Absidia in China is also provided herein. This is the first overview of the Absidia ecological habitat.